Surveillance of Infectious Diseases in Arizona - Wheeler, Naomi (My University, 2011)
This document describes various experiences of Kansas State University graduate student Naomi Wheeler during her field experience for a Master’s degree in Public Health and demonstrates her competent understanding of the principles of public health practice in relation to these field experiences. The student worked with the Arizona Department of Health Services, the Coconino County Health Department, the USDA Wildlife Services, and the Centers for Disease Control. With these organizations she worked in surveillance and control programs of rabies, West Nile virus, and Rocky Mountain Spotted Fever.
Keywords: Rabies; West Nile virus; Rocky Mountain Spotted Fever; Public Health (0573)